ERP evidence for Slavic and German word stress cue sensitivity in English - Ivanova, Marina; Neubert, Christiane R.; Schmied, Josef; Bendixen, Alexandra (Frontiers in Psychology, 2023)
Word stress is demanding for non-native learners of English, partly because speakers from different backgrounds weight perceptual cues to stress like pitch, intensity, and duration differently. Slavic learners of English and particularly those with a fixed stress language background like Czech and Polish have been shown to be less sensitive to stress in their native and non-native languages. In contrast, German English learners are rarely discussed in a word stress context. A comparison of these varieties can reveal differences in the foreign language processing of speakers from two language families. We use electroencephalography (EEG) to explore group differences in word stress cue perception between Slavic and German learners of English. Slavic and German advanced English speakers were examined in passive multi-feature oddball experiments, where they were exposed to the word impact as an unstressed standard and as deviants stressed on the first or second syllable through higher pitch, intensity, or duration. The results revealed a robust Mismatch Negativity (MMN) component of the event-related potential (ERP) in both language groups in response to all conditions, demonstrating sensitivity to stress changes in a non-native language. While both groups showed higher MMN responses to stress changes to the second than the first syllable, this effect was more pronounced for German than for Slavic participants. Such group differences in non-native English word stress perception from the current and previous studies are argued to speak in favor of customizable language technologies and diversified English curricula compensating for non-native perceptual variation.